INDENTIFIKASI FAKTOR-FAKTOR MEMPENGARUHI KINERJA BIAYA OPERASIONAL DAN PEMELIHARAAN JARINGAN IRIGASI D.I PAGUYAMAN - Djau, Rahman Abdul; Nento, Sartan; Hidayat, Andi Sahrul; -, Supriyadi (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2023)
This study aims to identify the factors that influence the performance of operational and maintenance costs in the DI irrigation network. Paguyaman. To achieve this goal, the researchers used a survey method by distributing questionnaires to a number of respondents who were involved in the implementation and monitoring of DI irrigation networks. Paguyaman. Data collection was carried out by way of a direct survey to the location and a list of questions in the questionnaire for primary data. As for the secondary data obtained from the literature and data from related agencies. Based on the results of the questionnaire from the respondents, a ranking was made of the causal factors that affect the performance of operational and maintenance costs in the DI irrigation network. Paguyaman. From the ranking results, there are 15 factors that are categorized as influential. The conclusions that can be drawn after statistical tests are that there are seven factors that influence the performance of operational costs and maintenance of irrigation networks in D.I Paguyaman. These factors are unexpected conditions and events (floods, earthquakes and others), general information and methods in carrying out operations and maintenance for field officers are inadequate, there is still a lack of responsibility for officers in carrying out irrigation operations and maintenance, changes in areas that encouraging the conversion of paddy fields to other users, the number of operational and maintenance officers is still lacking, the equipment is of poor quality and there is no training for P3A, and the most dominant factors affecting the performance of operational costs and maintenance of irrigation networks in D.I Paguyaman are conditions and events that unexpected events (floods, earthquakes, etc.).